The care of non-institutionalized ADL-dependent people in the Orcasitas neighborhood of Madrid (Spain) during the Covid-19 pandemic and its relationship with social inequalities, intergenerational dependency and survival - Martín Moreno, Vicente; Martínez Sanz, María Inmaculada; Martín Fernández, Amanda; Sánchez Rodríguez, Elena; Sánchez González, Irene; Herranz Hernando, Julia; Fernández Gallardo, Miriam; Recuero Vázquez, Miguel; Benítez Calderón, María Palma; Sevillano Fuentes, Eva; Pérez Rico, Elena; Calderón Jiménez, Laura; et al. (Frontiers in Public Health, 2024)
Background: ADL-dependent individuals die at a higher rate than others of the same age. Understanding the evolutionary course and factors involved in noninstitutionalized ADL-dependency, including the influence of the family structure that supports this population, would contribute to improved health planning.Methods: A longitudinal study was carried out on the entire ADL-dependent population of the Orcasitas neighborhood of Madrid, Spain, between June 2020, when nationwide COVID-19 lockdown ended, and June 2023. A total of 127 patients participated in the study, 78.7% of whom were women and 21.3% were men. Risk analysis was performed via odds ratios, and hazard ratios. Survival analysis was performed using Cox regression.Results: A total of 54.33% of the ADL-dependent persons did not live with their adult children and 45.67% did, being associated living independently with economic capacity and the married marital status, but not with the dependency level. In women, being married increased the probability of living independently of their adult children (OR 12.632;). Loss of mobility (OR 0,398; 95%CI 0,186-0,853), the economic capacity (HR 0.596; 95%CI 0.459-0.774) and living independently and having better economic capacity (HR 0.471; 95% 95%CI 0.234-0.935) were associated with 3year survival. Those who lived with their adult children had a worse autonomy profile and higher mortality (HR 1.473; 95%CI 1.072-2.024). Not having a job, not being married, and not owning a home were significantly associated with being an essential family caregiver. Carers were mostly female (OR 1.794; 95%CI 1.011-3.182).Conclusions: Among ADL-dependent people, economic capacity influenced the ability to maintain an independent life and affected survival after 3 years. Loss of mobility (wheelchair use) was a predictor of mortality. Social inequalities encourage children to end up being essential family caregivers, generating inverse dependency, and maintaining a vulnerability that transmitted from generation to generation and perpetuates social and gender inequalities. Caregiving for persons with ADL dependency maintained in this cohort an archaic pattern in which the eldest daughter cared for her parents. This study made it possible to show that ADL-dependence accompanied by complex interrelationships that must be considered in socio-health planning.